PROBLEMATIC ISSUES OF LEGAL REGULATION OF THE STATUS OF THE HEAD OF THE CIVIL SERVICE IN THE STATE BODY - Рябченко, Олена Петрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: analysis of the main problematic issues of legal regulation of the status of the head of the civil service in a state body, the presence of which affects the implementation of the state service legal status by the head. Methods: the system approach combined with the comparative legal method and structural analysis allowed to distinguish the purpose of the function of the head of the civil service being an official of the executive authorities and to identify the key problems of legal regulation of his status. Outcomes: it is indicated that the competence of the head of the civil service is directed at the organization, ensuring the manageability of the activities of the staff of the state body. The present paper outlines the relations within which the competence of the head of the civil service is realized: holding competitions for vacancies in the civil service of the specified categories; staff rotation; assignment of ranks; appointment to a post and dismissal; vocational training planning; advanced training; control over observance of the executive discipline; implementation of disciplinary rights; creation of proper conditions for work of the staff; performance of the employer’s function in relation to employees of a public authority who are not civil servants. The problematic issues of legal regulation of the status of the head of the civil service in the state body include: the existence of mutually exclusive norms, which regulate the status of the Minister of the Cabinet of Ministers of Ukraine being the head of the state service, the absence of application of the procedure for conducting a competition for vacancy in the state service of the heads of local state administrations, their first deputies and deputies. Discussion: in this article the author revealed gaps and conflicts of legal regulation of the status of the head of the civil service, the elimination of which requires the formation of a holistic view towards the functionality of the head of the civil service.